Unidades de paisagem do Polo Mota, reserva extrativista Marinha de Maracanã-Maracanã-Pará - SILVA, Stefany de Paula Pereira da (2022)
The present work aims to identify, classify and map the landscape units of the Polo Mota, located in the municipality of Maracanã, northeast of the state of Pará. The methodology of Georges Bertrand (2004) , biological exploitation and anthropic action. Thus, four geosystems were mapped: geosystems of external sandy strings under tourist activity, geosystem of pioneer formations of the halophyte forests in the tidal plain under extractive exploitation, geosystem of the pioneer formations of restinga of the internal sandy cords, geossystem of secondary vegetation of the low plateaus and traps with rural and urban occupation, and twelve geofacies: sandy beach barrier geophysics, sandstone-lamoso tidal shoals geophysics, mangrove geophysics presenting Rysophora mangle, intermarine zone geophysics, covered by herbaceous restinga, with predominance of Sporobolus virginicus (L.) Kunth; dune geophysics covered by shrub restinga, with predominance of Chrysobalanus icaco L; surface covered by restinga forest, with presence of Byrsonima crassifolia (L.) Kunth ;, - cliffs geophysics carved in argillites and sandstones of the barrier formation, ferruginous sandstone abrasion platform geofácies, surface excavated by mineral extractive activity, surface area for commercial use, surface cultivated with Manihot esculenta Crantz, surface covered with secondary vegetation, with predominance of Astrocaryum aculeatum, Meyer. The identification of these units offers to the environmental planning subsidies that can aid in the decision making, since they show the spatial disposition of the natural resources and their respective uses, therefore, of the potentialities and fragilities of the study area.